The impact of city-county mergers on urban land green utilization efficiency: evidence from China - Zhao, MengChao; Xiao, Xiang; Le, Yang (Frontiers in Environmental Science, 2024)
As an urbanization effort propelled by administrative measures, city-county merger has been particularly prevalent in the administrative district adjustments of prefecture-level cities in China.However, there has been scant research focusing on the policy's impact on the efficiency of green utilization of urban land. We selected panel data from Chinese prefecture-level cities from 2003 to 2020, employing the slack-based measure (SBM) model that accounts for undesirable outputs, in conjunction with the Malmquist-Luenberger (ML) productivity index, to measure the efficiency of green land use in cities. Building on this, we utilized the staggered difference-in-differences (DID) model to investigate the impact of policies expanding cities through land leasing on the green utilization efficiency of urban land. Our findings indicate that the city-county merger has generally led to a decline in the efficiency of green utilization of urban land. Further mechanism analysis suggests that local governments' excessive focus on land leasing for economic development, leading to a low-quality development model, is a significant factor contributing to the decline in green utilization efficiency of urban land. Specifically, the city-county merger policy indirectly reduces land green utilization efficiency by increasing industrial land leasing revenue, the number of industrial polluting enterprises, lowering the rationalization level of urban industrial structure, and raising the overachievement of urban economic growth targets. Further research reveals that the policy has heterogeneous impacts on land green utilization efficiency across different regions, city sizes, administrative levels, economic development levels, and urban planning types. The policy has a more significant inhibitory effect on land green utilization efficiency in non-eastern regions, smaller cities, peripheral cities, underdeveloped cities, and resource-based cities. Our study confirms that as a significant urbanization reform initiative, the effectiveness of the city-county merger still relies on the traditional extensive growth model based on land expansion, which is not conducive to enhancing the efficiency of green land use in cities.